Budaya Batak Toba dalam Pelayanan Pariwisata Danau Toba di Parapat - Eka Debora Harianja; R. Hamdani Harahap; Zulkifli Lubis (Universitas Medan Area, 2021)
Toba Batak culture is very important for the development of Lake Toba tourism in Parapat. Toba 3H Batak culture (Hamoraon, Hagabeon, and Hasangapon) is a culture that is strongly held by the Toba Batak people. And the culture is carried out in daily living habits including the way the Toba Batak people in Parapat treat tourists and if tourists are satisfied, of course there will be tourism development. So in this study will look at the attitudes, attention, actions, and anticipation of tourism actors both local Toba Batak communities, business people and related parties in increasing the development of tourism in Parapat. The methodology used in this research is qualitative research with a descriptive approach. The informants in this study were key informants in this study were tribal chiefs who knew Batak culture well, the main informants in this study were domestic tourists with Toba Batak and foreign tourists who ended up in Parapat and additional informants in this study were business actors and givers tourism services such as traders, hotel entrepreneurs, restaurant entrepreneurs, hotel servants, restaurant servants, parking attendants, etc., and tourism observers and responsible government agencies such as the Tourism Office and BPS The results of this study indicate that Batak Toba culture can have a positive and negative impact on Lake Toba tourism, but in this study it was seen that Batba Toba 3H culture had a negative impact on the development of tourism. It can be seen how the Toba Batak people serve tourists. The obstacles faced are the habit of the Batak Toba people who are very hard and want to be respected, making tourists not want to return to Parapat